Forbidding wrong in Islam an introduction - Cook, Michael 1940- (Cambridge University Press, 2003)
Michael Cook's magisterial study in Islamic ethics, Commanding Right and Forbidding Wrong in Islamic Thought, was published to much acclaim in 2001. It was described by one reviewer as a masterpiece. In that book, the author reflected on the Islamic injunction, incumbent on every Muslim, to forbid wrongdoing. The present book is a short, accessible survey of the same material. Using anecdotes and stories from Islamic sources to illustrate the argument, Cook unravels the complexities of the subject. Moving backwards and forwards through time, he demonstrates how the past informs the present. By the end, the reader will be familiar with a colourful array of characters from Islamic history ranging from the celebrated thinker Ghazzali, to the caliph Harun al-Rashid, to the Ayatollah Khumayni. The book educates and entertains - at its heart, however, is an important message about the Islamic tradition, its values, and the relevance of those values today
Title from publisher's bibliographic system (viewed on 05 Oct 2015)
Keywords: Islamic ethics; Muslims / Conduct of life; Islamic philosophy; Ethik; Islam; Rechtsschule; Religiöses Leben